Design and fabrication of bimetallic oxide nanonest-like structure/carbon cloth composite electrode for supercapacitors. Issue 21 (1st November 2021) - Javed, Muhammad Sufyan; Khan, Abdul Jabbar; Ahmad, Awais; Siyal, Sajid Hussain; Akram, Shakeel; Zhao, Guowei; Awadh Bahajjaj, Aboud Ahmed; Ouladsmane, Mohamed; Alfakeer, Majda
Abstract: It's crucial to fabricate commercial-level electrodes with high mass loading of active materials for supercapacitors (SCs) to address the growing need for commercial-level flexible energy storage devices. In this work, we reported the direct growth of ZnCo2 O4 nanonest-like structure composed of nanowires with high mass loading (5 mg cm −2 ) on the substrate of carbon cloth (CC, hereafter denoted as ZnCo2 O4 @CC) via a simple hydrothermal method. The ZnCo2 O4 @CC electrode was characterized by a variety of techniques including SEM/TEM, XRD/XPS, and BET/BJH. The ZnCo2 O4 @CC electrode possesses a holey characteristic with various electroactive sites for the utilization of electrolyte and delivered high specific capacitance of 1467 (1320 C g -1 ) Fg −1 at 1.2 Ag -1 with outstanding cycling retention of 95% at 12 Ag -1 and high Coulombic efficiency after 10, 000 cycles. In addition, we employed power's law to explore the charge storage kinetics of ZnCo2 O4 @CC electrode to investigate the capacitive and diffusion-controlled charge storage quantification. The ZnCo2 O4 @CC electrode displayed high capacitive storage properties (42% capacitive at 15 mVs −1 ). Thus, the admirable electrochemical performance of the ZnCo2 O4 electrode highlights the potential application in supercapacitors for future endowers. Graphical abstract: The ZnCo2 O4 @CC electrode possesses a holey characteristic with various electroactive sites for the fully utilization of electrolyte and delivered excellent rate-capability and exceptional cycling stability. Image 1 Highlights: ZnCo2 O4 @CC electrode composed by nanowires synthesized via a simple hydrothermal method for supercapacitor's electrode. Binder-free ZnCo2 O4 @CC electrode exhibits excellent specific capacitance of 1467 (1320 C g -1 ) Fg −1 at 1.2 Ag -1 . The ZnCo2 O4 @CC electrode delivered high capacitance retention of 95% after 10, 000 cycles. The ZnCo2 O4 @CC electrode possesses hybrid-kind of charge storage properties.